Murinocardiopsis flavida gen. nov., sp. nov., an actinomycete isolated from indoor walls - Kämpfer, Peter; Schäfer, Jenny; Lodders, Nadine; Martin, Karin; Justus Liebig University Giessen (My University, 2009)
Two Gram-stain-positive, mycelium-forming actinobacteria (strains 14-Be-013T and 02-Gi-014) were isolated from walls colonized with moulds and studied taxonomically. The isolates formed yellowish-pigmented substrate mycelium showing no fragmentation. Comparative analysis of 16S rRNA gene sequences showed that these bacteria are most closely related to genera within the family Nocardiopsaceae, but form a separate lineage within this family. Highest sequence similarities were to the type strains of Marinactinospora thermotolerans (96.0% to 14-Be-013T), Nocardiopsis dassonvillei subsp. albirubida and Nocardiopsis lucentensis (both 95.3% to 14-Be-013T). Whole-cell hydrolysates contained meso-diaminopimelic acid as the diagnostic diamino acid of the cell wall and no diagnostic sugars. Mycolic acids were absent. The major menaquinones were MK-10(H4), MK-11(H4) and MK-12(H2). The polar lipid profile consisted of phosphatidylcholine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol and unknown lipids. Major fatty acids iso-C16:0, anteiso-C17:0 and C18:1?9c supported the affiliation of these isolates to the family Nocardiopsaceae. Phenotypic analysis (including chemotaxonomy) further differentiated strains 14-Be-013T and 02-Gi-014 from the most closely related members of the genera Marinactinospora and Nocardiopsis. Since the two strains form a distinct lineage in the 16S rRNA gene sequence-based phylogenetic tree, the novel genus Murinocardiopsis gen. nov. with the type species Murinocardiopsis flavida sp. nov. is proposed. The type strain of Murinocardiopsis flavida is 14-Be-013T (=DSM 45312T =CCM 7612T).
Keywords: Murinocardiopsis gen. nov.; Murinocardiopsis flavida sp. nov.; Actinomycetes; ddc:570